Political Representation of Gender in Nepal - Sijapati, Dipendra Bikram (Patan Pragya, 2021)
This paper is based on qualitative methods and discusses women's struggle for equal political participation, currently successful in the political representation of gender in Nepal. The aim of this paper is to examine the establishing equal representation in all sectors of elected government and to find out the inclusive participation of male and female in Nepalese, politics and parliament in together. It is based on completely secondary sources of data through the published in different governmental (election commission, 2074) and non-governmental organization. Nepal has been undergoing tremendous socio-political transformations over the past three decades, unitary to federal and monarchical government to the current republican political system; Nepali women have established themselves as key actors of socio-political changes. Nepali women began their struggle during the Rana Regime and advanced since the 1950s, by engaging both in popular peaceful political movements to armed insurgency and parliamentary competition with their male political counterparts. As a result, latest constitution of Nepal ensured 33% of seats are guaranteed to the parliaments and all other government positions as well as provision of male-female alternates eat provisions. As a result, from the national and local elections of 2017-18, women have come to occupy 41.8 percent political positions across the country. One of the key factors to ensure higher and meaningful participation of women in politics was these favorable electoral provisions. Women have demonstrated success in achieving higher participation in political positions. However, what has been achieved so far is not enough and continued rigorous action among all actors is essential.